Lusophone media and communication studies: imperial nostalgia or transcontinental communicative space? - Sousa, Helena (2018)
[Excerto] This Crosscurrents Special Section maps and critically examines media and communication studies in Portuguese speaking countries worldwide (Angola, Brazil, Cape Verde, Equatorial Guinea, Guinea Bissau, Mozambique, Portugal and S. Tome and Principe, East-Timor).[...]